In the picture : a first word book - Petty, Kate; Clements, Gillian (London, Award, 1992)
What's going on in the picture? is carefully designed so that children will learn new words in context. From dinosaur world to shopping mall and on a beach, each picture spread illustrates and labels a busy, popular and contemporary theme. It offers over 2,000 new words to identify, understand and enjoy, and is a vital aid to this important stage of early learning.